Preparation method of uvioresistant air layer knitted fabric
Through the combined structure of seaweed fiber and silica aerogel, high breathability and long-term UV resistance fabrics are formed, which solves the problems of poor breathability and insufficient UV resistance of existing sunscreen fabrics, and provides better sun protection effect and comfort.
Patent Information
- Application Number
- CN202411456156.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-03
AI Technical Summary
The existing sunscreen fabrics are poorly breathable in hot summers, resulting in sweat accumulation and a stuffy feeling. At the same time, they cannot effectively prevent excessive UV damage and are insufficient in UV resistance.
Using seaweed fiber fabric layer-air layer-seaweed fiber fabric structure, special-shaped cross-sectional fibers are formed by extrusion and spinning, and under the synergistic action of silica aerogel, zinc ions and alginic acid are used to form a stable salt structure, combined with The silica aerogel with holes penetrated as an air layer to enhance breathability and ultraviolet reflection effect.
It achieves high breathability and long-term anti-UV properties, prevent direct UV rays, reduce skin damage, and avoids sweat accumulation and stuffy feeling.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabrics, in particular to a method for preparing an anti-ultraviolet air layer knitted fabric. Background Art
[0002] Most of the creatures on the earth, especially humans, cannot live without sunlight, which includes ultraviolet radiation. The existence of the ozone layer can reduce excessive ultraviolet radiation directly hitting the earth's surface and protect the earth's creatures. However, with the pollution of the atmosphere by industrial waste gas, the ozone layer has been destroyed, becoming thinner and thinner year by year and holes appearing. The short-wave UVC part transmitted to the earth has an increasing trend. The damage caused by excessive ultraviolet rays to human skin has made humans clearly realize that the skin is a weak link in the human body and it is susceptible to various external injuries. As a result, human self-protection awareness has been continuously strengthened. Especially in the hot summer, people's skin is directly exposed to the sun for a long time, which will make the skin darker, produce spots, cause inflammation and many other pathological phenomena, causing more and more people to be troubled, and the body often perspires a lot. Wearing ordinary clothes with sun protection function has a feeling of being airtight, and then sweat makes the clothes feel sticky and stuffy close to the body. Therefore, in order to avoid these uncomfortable feelings and prevent ultraviolet rays from continuing to harm human health, it is particularly necessary to invent an anti-ultraviolet air layer knitted fabric. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing an anti-ultraviolet air layer knitted fabric to solve the problems existing in the prior art.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: an anti-ultraviolet air layer knitted fabric, wherein the structure of the anti-ultraviolet air layer knitted fabric is seaweed fiber fabric layer-air layer-seaweed fiber fabric layer; The preparation method of the anti-ultraviolet air layer knitted fabric comprises the following preparation steps: (1) Sodium alginate and deionized water were mixed in a mass ratio of 2-6:95-120, heated to 40-60°C, stirred at 120-320 rpm for 3-6 hours, filtered, allowed to stand for 24 hours, extruded and spun using a three-leaf profiled spinneret, placed in a coagulation bath, ultrasonicated at 21 kHz for 1-2 hours, allowed to stand for 5-10 hours, placed in a 10 wt% sodium hydroxide aqueous solution for reaction for 2-6 hours, washed once with deionized water, placed in a 40 wt% ethylene glycol aqueous solution, stirred at 80-120 rpm for 20 hours, then stretched, washed 3-5 times with deionized water, dried at 40°C for 8-12 hours, and woven to a weight of 50-100 g / m 2 Seaweed fiber fabric; (2) Mix tetraethyl orthosilicate, ethanol and deionized water, stir at 100-150 rpm for 30-60 min, add 0.9 wt% hydrochloric acid aqueous solution until the solution pH is 2-3, heat to 50 °C, stir at 120-200 rpm for 60-120 min, add N,N-dimethylformamide, let stand for 24 h, add ammonia water until the solution pH is 7-8, age in 70 wt% tetraethyl orthosilicate-ethanol solution at 40 °C, wash with deionized water at 40 °C for 1-3 times, and finally dry at -35--65 °C and vacuum degree of 0.5-1 Pa for 24-48 h to obtain silica aerogel with a thickness of 0.5-1 mm; (3) The seaweed fiber fabric is compounded on the upper and lower layers of the silica aerogel respectively through an adhesive, and baked at 100-120°C for 20-40 minutes to obtain an anti-ultraviolet air layer knitted fabric.
[0005] Furthermore, the filtering conditions in step (1) are: the pressure is 0.3 MPa, and the filter membrane is a polypropylene filter membrane with a pore size of 209 mm.
[0006] Furthermore, the extrusion spinning speed in step (1) is 1550 m / min.
[0007] Furthermore, the coagulation bath in step (1) is prepared by mixing calcium chloride, zinc sulfate and deionized water in a mass ratio of 4:1.7:100.
[0008] Furthermore, the drafting ratio in step (1) is 150%.
[0009] Furthermore, the aging time in step (2) is 48 hours.
[0010] Furthermore, in step (2), the mass ratio of ethyl orthosilicate, ethanol, deionized water and N,N-dimethylformamide is 1:6~10:3~5:0.8~1.
[0011] Furthermore, the adhesive in step (3) is a polyurethane adhesive.
[0012] Furthermore, the dosage of the adhesive in step (3) is 15-20 g / m 2 .
[0013] Furthermore, the baking time in step (3) is 20 to 40 minutes.
[0014] Compared with the prior art, the beneficial effects achieved by the present invention are: The fabric of the present invention utilizes silica aerogel with holes through it as an air layer, and the structure of the fabric is seaweed fiber layer-aerogel air layer-seaweed fiber layer. The special-shaped cross-sectional structure of the seaweed fiber enables the fiber layer to form an internal cavity, which cooperates with the three-dimensional network structure of the aerogel to enhance the air permeability of the fabric. The cavity and the fiber itself partially divide the holes on the contact surface between the two, making it difficult for sunlight to directly enter the fabric, thereby enhancing the ultraviolet reflection effect. In addition, the ultraviolet absorption of the silica aerogel works together to improve the anti-ultraviolet effect of the fabric.
[0015] The present invention extrudes sodium alginate into special-section fibers through extrusion spinning, so that the cross-section of the fiber presents an irregular shape and a groove shape in the longitudinal direction, so that a good capillary effect is generated on the fiber surface, which is beneficial to air conduction, thereby achieving a breathable effect. Then, the fiber is immersed in a zinc sulfate solution. With the assistance of ultrasonic waves, the negatively charged carboxyl groups in the sodium alginate can attract each other with the positively charged zinc ions, so that the zinc sulfate can be filled in the grooves of the seaweed fiber, and as the immersion time increases, the zinc ions are adsorbed into the fiber, so that the zinc ions evenly distributed inside and outside the fiber react with the sodium hydroxide added in the subsequent water washing process to be converted into zinc oxide particles, so that the fiber achieves an anti-ultraviolet effect. Since the zinc ions form a stable salt structure with the alginate, the zinc oxide particles can be stably loaded or embedded in the fiber, so as to achieve long-term anti-ultraviolet performance. DETAILED DESCRIPTION
[0016] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0017] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the anti-ultraviolet air layer knitted fabrics prepared in the following examples are as follows: Anti-ultraviolet: The transmittance of the embodiment and the comparative example of the same size between 290 and 400 nm was tested on a HITACHI-3310 UV-visible spectrophotometer, and the UPF value of the fabric was calculated with reference to GB / T18830; and the samples were machine washed with 2g / L soap solution for 10 minutes and washed with tap water for 2 minutes, and the anti-ultraviolet test was performed to calculate the UPF value.
[0018] Air permeability: Take the embodiment and comparative example of the same size and refer to GB / T5453, use a full-automatic air permeability tester, and test the air permeability at a temperature of 20°C, a relative humidity of 65%, and a pressure difference of 100Pa for 24 hours.
[0019] Example 1; (1) Calcium chloride, zinc sulfate and deionized water were mixed in a mass ratio of 4:1.7:100 to obtain a coagulation bath; sodium alginate and deionized water were mixed in a mass ratio of 2:95, the temperature was raised to 40°C, stirred at 120rpm for 3h, filtered through a polypropylene filter membrane with a pressure of 0.3MPa and a pore size of 209mm, allowed to stand for 24h, extruded and spun using a three-leaf special-shaped spinneret at a speed of 1550m / min, placed in a coagulation bath, ultrasonicated at 21kHz for 1h, allowed to stand for 5h, placed in a 10wt% sodium hydroxide aqueous solution for reaction for 2h, washed once with deionized water, placed in a 40wt% ethylene glycol aqueous solution, stirred at 80rpm for 20h, then stretched at a stretching ratio of 150%, washed three times with deionized water, dried at 40°C for 8h, and woven to obtain a gram weight of 50g / m 2 Seaweed fiber fabric; (2) TEOS, ethanol and deionized water were mixed, stirred at 100 rpm for 30 min, 0.9 wt% hydrochloric acid aqueous solution was added until the solution pH was 2, the temperature was raised to 50°C, stirred at 120 rpm for 60 min, N,N-dimethylformamide was added, the solution was allowed to stand for 24 h, ammonia water was added until the solution pH was 7, and the solution was aged in a 70 wt% hexyl orthosilicate-ethanol solution at 40°C for 48 h, then washed once with deionized water at 40°C, and finally dried at -35°C and a vacuum degree of 0.5 Pa for 24 h to obtain a silica aerogel layer with a thickness of 0.5 mm; the mass ratio of TEOS, ethanol, deionized water and N,N-dimethylformamide was 1:6:3:0.8; (3) The seaweed fiber fabric is compounded on the upper and lower layers of the silica aerogel by a polyurethane adhesive, and the adhesive dosage is 15g / m 2 , baked and shaped at 100°C for 20 minutes to obtain an anti-ultraviolet air layer knitted fabric.
[0020] Example 2; (1) Calcium chloride, zinc sulfate and deionized water were mixed in a mass ratio of 4:1.7:100 to obtain a coagulation bath; sodium alginate and deionized water were mixed in a mass ratio of 4:110, the temperature was raised to 50°C, stirred at 220rpm for 4.5h, filtered through a polypropylene filter membrane with a pressure of 0.3MPa and a pore size of 209mm, allowed to stand for 24h, extruded and spun using a three-leaf special-shaped spinneret at a speed of 1550m / min, placed in a coagulation bath, ultrasonicated at 21kHz for 1.5h, allowed to stand for 8h, placed in a 10wt% sodium hydroxide aqueous solution for reaction for 4h, washed once with deionized water, placed in a 40wt% ethylene glycol aqueous solution, stirred at 100rpm for 20h, then stretched at a stretching ratio of 150%, washed four times with deionized water, dried at 40°C for 10h, and woven to obtain a gram weight of 75g / m 2 Seaweed fiber fabric; (2) TEOS, ethanol and deionized water were mixed, stirred at 125 rpm for 45 min, 0.9 wt% hydrochloric acid aqueous solution was added until the solution pH was 2.5, the temperature was raised to 50°C, stirred at 160 rpm for 90 min, N,N-dimethylformamide was added, the solution was allowed to stand for 24 h, ammonia water was added until the solution pH was 7.5, and the solution was aged in a 70 wt% hexyl orthosilicate-ethanol solution at 40°C for 48 h, then washed twice with deionized water at 40°C, and finally dried at -50°C and a vacuum degree of 0.75 Pa for 36 h to obtain a silica aerogel layer with a thickness of 0.75 mm; the mass ratio of TEOS, ethanol, deionized water and N,N-dimethylformamide was 1:8:4:0.9; (3) The seaweed fiber fabric is compounded on the upper and lower layers of the silica aerogel by a polyurethane adhesive, and the adhesive dosage is 18g / m 2 , baked and shaped at 110°C for 30 minutes to obtain an anti-ultraviolet air layer knitted fabric.
[0021] Example 3; (1) Calcium chloride, zinc sulfate and deionized water are mixed in a mass ratio of 4:1.7:100 to obtain a coagulation bath; sodium alginate and deionized water are mixed in a mass ratio of 6:120, the temperature is raised to 60°C, stirred at 320rpm for 6h, filtered through a polypropylene filter membrane with a pressure of 0.3MPa and a pore size of 209mm, allowed to stand for 24h, extruded and spun using a three-leaf special-shaped spinneret at a speed of 1550m / min, placed in a coagulation bath, ultrasonicated at 21kHz for 2h, allowed to stand for 10h, placed in a 10wt% sodium hydroxide aqueous solution for reaction for 6h, washed once with deionized water, placed in a 40wt% ethylene glycol aqueous solution, stirred at 120rpm for 20h, then stretched at a stretching ratio of 150%, washed 5 times with deionized water, dried at 40°C for 8-12h, and woven to obtain a gram weight of 100g / m 2 Seaweed fiber fabric; (2) TEOS, ethanol and deionized water were mixed, stirred at 150 rpm for 60 min, 0.9 wt% hydrochloric acid aqueous solution was added until the solution pH was 3, the temperature was raised to 50°C, stirred at 200 rpm for 120 min, N,N-dimethylformamide was added, the solution was allowed to stand for 24 h, ammonia water was added until the solution pH was 8, and the solution was aged in a 70 wt% hexyl orthosilicate-ethanol solution at 40°C for 48 h, then washed with deionized water at 40°C for 3 times, and finally dried at -65°C and a vacuum degree of 1 Pa for 48 h to obtain a silica aerogel layer with a thickness of 1 mm; the mass ratio of TEOS, ethanol, deionized water and N,N-dimethylformamide was 1:10:5:1; (3) The seaweed fiber fabric is compounded on the upper and lower layers of the silica aerogel by a polyurethane adhesive, and the adhesive dosage is 20g / m 2, baked and shaped at 120°C for 40 minutes to obtain an anti-ultraviolet air layer knitted fabric.
[0022] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that step (1) is different. Step (1) is changed to: calcium chloride, zinc sulfate and deionized water are mixed in a mass ratio of 4:1.7:100 to obtain a coagulation bath; sodium alginate and deionized water are mixed in a mass ratio of 4:110, the temperature is raised to 50°C, stirred at 220rpm for 4.5h, filtered through a polypropylene filter membrane with a pressure of 0.3MPa and a pore size of 209mm, allowed to stand for 24h, and extruded and spun. The spinneret aperture is 1.01 mm, the speed is 1550 m / min, placed in a coagulation bath, 21 kHz ultrasound for 1.5 h, and after standing for 8 h, placed in a 10 wt% sodium hydroxide aqueous solution for 4 h, washed once with deionized water, and then placed in a 40 wt% ethylene glycol aqueous solution, stirred at 100 rpm for 20 h, and then stretched with a stretching ratio of 150%, washed 4 times with deionized water, and dried at 40 ° C for 10 h. The woven weight is 75 g / m 2 Seaweed fiber fabric; the remaining steps are the same as in Example 2.
[0023] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that step (1) is different. Step (1) is changed to: calcium chloride, zinc sulfate and deionized water are mixed in a mass ratio of 4:1.7:100 to obtain a coagulation bath; sodium alginate and deionized water are mixed in a mass ratio of 4:110, heated to 50°C, stirred at 220rpm for 4.5h, filtered through a polypropylene filter membrane with a pressure of 0.3MPa and a pore size of 209mm, allowed to stand for 24h, extruded and spun using a three-leaf special-shaped spinneret at a speed of 1550m / min, placed in a coagulation bath, allowed to stand for 3h, placed in a 10wt% sodium hydroxide aqueous solution for reaction for 4h, washed once with deionized water, and then placed in a 40wt% ethylene glycol aqueous solution, stirred at 100rpm for 20h, then stretched, with a stretching ratio of 150%, washed 4 times with deionized water, dried at 40°C for 10h, and woven to obtain a gram weight of 75g / m 2 Seaweed fiber fabric; the remaining steps are the same as in Example 2.
[0024] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that step (1) is different, and step (1) is changed to: sodium alginate and deionized water are mixed in a mass ratio of 4:110, heated to 50°C, stirred at 220rpm for 4.5h, filtered at a pressure of 0.3MPa and a pore size of 209mm for polypropylene filter membrane, allowed to stand for 24h, extruded and spun using a three-leaf special-shaped spinneret at a speed of 1550m / min, placed in a 4wt% calcium chloride aqueous solution, allowed to stand for 8h, placed in a 10wt% sodium hydroxide aqueous solution for reaction for 4h, washed once with deionized water, and then placed in a 40wt% ethylene glycol aqueous solution, stirred at 100rpm for 20h, then stretched, the stretching ratio was 150%, washed 4 times with deionized water, dried at 40°C for 10h, and the woven weight was 75g / m 2 Seaweed fiber fabric; the remaining steps are the same as in Example 2.
[0025] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that step (1) is different. Step (1) is changed to: calcium chloride, zinc sulfate and deionized water are mixed in a mass ratio of 4:1.7:100 to obtain a coagulation bath; sodium alginate and deionized water are mixed in a mass ratio of 4:110, the temperature is raised to 50°C, stirred at 220rpm for 4.5h, filtered through a polypropylene filter membrane with a pressure of 0.3MPa and a pore size of 209mm, allowed to stand for 24h, extruded and spun using a three-leaf special-shaped spinneret at a speed of 1550m / min, placed in a coagulation bath, ultrasonicated at 21kHz for 1.5h, allowed to stand for 8h, washed once with deionized water, and then stretched at a stretching ratio of 150%, washed 4 times with deionized water, dried at 40°C for 10h, and woven to a gram weight of 75g / m 2 Seaweed fiber fabric; the remaining steps are the same as in Example 2.
[0026] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that there is no step (2), and step (3) is changed to: compounding the two layers of seaweed fiber fabrics with a polyurethane adhesive, and the adhesive dosage is 18g / m 2 , baking and shaping at 110° C. for 30 minutes to obtain an anti-ultraviolet air layer knitted fabric; the remaining steps are the same as those in Example 2.
[0027] Effect example Table 1 below shows the performance analysis results of the anti-ultraviolet air layer knitted fabrics of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0028] From the comparison of the experimental data of the embodiment and the comparative example in Table 1, it can be found that the present invention extrudes sodium alginate into a special-section fiber by extrusion spinning, so that the cross-section of the fiber presents an irregular shape and a groove-shaped longitudinal shape, which is conducive to air conduction, thereby achieving a breathable effect. Then, it is immersed in a zinc sulfate solution, and with the assistance of ultrasound, it is filled in the grooves of the seaweed fiber, so that the fiber achieves an anti-ultraviolet effect, and as the immersion time increases, zinc ions are adsorbed into the fiber, and react with the sodium hydroxide added in the subsequent washing process to be converted into zinc oxide particles, and the zinc ions and alginate form a stable A certain salt structure is formed, so that the matrix can achieve long-term anti-ultraviolet performance; then, the silica aerogel with holes running through it is used as an air layer, so that the structure of the prepared fabric is seaweed fiber layer-aerogel air layer-seaweed fiber layer. The special-shaped cross-sectional structure of the seaweed fiber allows the fiber layer to form an internal cavity, which synergizes with the three-dimensional network structure of the aerogel to enhance the air permeability of the fabric. The cavity and the fiber itself partially divide the holes on the contact surface between the two, making it difficult for sunlight to directly enter the fabric, thereby enhancing the ultraviolet reflection effect. In addition, the ultraviolet absorption of the silica aerogel works together to improve the anti-ultraviolet effect of the fabric.
[0029] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. An anti-ultraviolet air layer knitted fabric, characterized in that: The structure of the anti-ultraviolet air layer knitted fabric is seaweed fiber fabric layer-air layer-seaweed fiber fabric layer; The preparation method of the anti-ultraviolet air layer knitted fabric comprises the following preparation steps: (1) Sodium alginate and deionized water were mixed in a mass ratio of 2-6:95-120, heated to 40-60°C, stirred at 120-320 rpm for 3-6 hours, filtered, allowed to stand for 24 hours, extruded and spun using a three-leaf profiled spinneret, placed in a coagulation bath, ultrasonicated at 21 kHz for 1-2 hours, allowed to stand for 5-10 hours, placed in a 10 wt% sodium hydroxide aqueous solution for reaction for 2-6 hours, washed once with deionized water, placed in a 40 wt% ethylene glycol aqueous solution, stirred at 80-120 rpm for 20 hours, then stretched, washed 3-5 times with deionized water, dried at 40°C for 8-12 hours, and woven to a weight of 50-100 g / m 2 Seaweed fiber fabric; (2) Mix tetraethyl orthosilicate, ethanol and deionized water, stir at 100-150 rpm for 30-60 min, add 0.9 wt% hydrochloric acid aqueous solution until the solution pH is 2-3, heat to 50 °C, stir at 120-200 rpm for 60-120 min, add N,N-dimethylformamide, let stand for 24 h, add ammonia water until the solution pH is 7-8, age in 70 wt% tetraethyl orthosilicate-ethanol solution at 40 °C, wash with deionized water at 40 °C for 1-3 times, and finally dry at -35--65 °C and vacuum degree of 0.5-1 Pa for 24-48 h to obtain silica aerogel with a thickness of 0.5-1 mm; (3) The seaweed fiber fabric is compounded on the upper and lower layers of the silica aerogel respectively by means of an adhesive, and baked at 100-120°C to be shaped, thereby obtaining an anti-ultraviolet air layer knitted fabric.
2. The anti-ultraviolet air layer knitted fabric according to claim 1, characterized in that: The filtering conditions in step (1) are as follows: the pressure is 0.3 MPa and the filter membrane is a polypropylene filter membrane with a pore size of 209 mm.
3. The anti-ultraviolet air layer knitted fabric according to claim 1, characterized in that: The extrusion spinning speed in step (1) is 1550 m / min.
4. The anti-ultraviolet air layer knitted fabric according to claim 1, characterized in that: The coagulation bath in step (1) is prepared by mixing calcium chloride, zinc sulfate and deionized water in a mass ratio of 4:1.7:
100.
5. The anti-ultraviolet air layer knitted fabric according to claim 1, characterized in that: The drafting ratio in step (1) is 150%.
6. The anti-ultraviolet air layer knitted fabric according to claim 1, characterized in that: The aging time in step (2) is 48 hours.
7. The anti-ultraviolet air layer knitted fabric according to claim 1, characterized in that: The mass ratio of tetraethyl orthosilicate, ethanol, deionized water and N,N-dimethylformamide in step (2) is 1:6~10:3~5:0.8~1.
8. The anti-ultraviolet air layer knitted fabric according to claim 1, characterized in that: The adhesive in step (3) is a polyurethane adhesive.
9. The anti-ultraviolet air layer knitted fabric according to claim 1, characterized in that: The dosage of the adhesive in step (3) is 15-20 g / m 2 .
10. The anti-ultraviolet air layer knitted fabric according to claim 1, characterized in that: The baking time in step (3) is 20 to 40 minutes.
Citation Information
Cited By
Fiber for air layer knitted fabric and preparation method thereof
CN121556175A